Large-eddy simulation of fluid mixing in tee with sintered porous medium - 王永伟 卢涛 姜培学 成鹏飞 王奎升 (Applied mathematics and mechanics, 2012)
Mixing processes of hot and cold fluids in a tee with and without sin- tered copper spheres are simulated by FLUENT using the large-eddy simulation （LES） turbulent flow model and the sub-grid scale （SGS） Smagorinsky-Lilly （SL） model with buoyancy. Comparisons of numerical results of the two cases with and without sintered copper spheres show that the porous medium significantly reduces velocity and temper- ature fluctuations because the porous medium can effectively restrict the fluid flow and enhance heat transfer. The porous medium obviously increases the pressure drop in the main duct. The porous medium reduces the power spectrum density （PSD） of tempera- ture fluctuations in the frequency range from 1 Hz to 10 Hz.